Influence of Grain Boundary on the Fatigue Crack Growth of 7050-T7451 Aluminum Alloy Based on Small Time Scale Method - Weihan Wang; Weifang Zhang; Hongxun Wang; Xiaoliang Fang; Xiaobei Liang (Advances in Materials Science and Engineering)
Based on the small time scale method, the influence of grain boundary on the fatigue crack growth of 7050-T7451 has been investigated. The interaction between fatigue crack and grain boundary was investigated by in situ SEM testing. Results showed that the fatigue crack growth will be retarded by grain boundary when the angle between fatigue crack and grain boundary is greater than 90 degrees. Mechanism analysis showed that the fatigue crack tip would not be able to open until the loading reached the 55% of maximum load, and the fatigue crack had been closed completely before the loading was not reduced to the minimum value, which led to the crack growth retardation. When the 7050-T7451 aluminum alloy suffered from fatigue loading with constant amplitude, a behavior of unstable fatigue crack growth could be observed often, and results indicated that the bridge linked mechanism led to the behavior. The grain boundary was prone to fracture during fatigue loading, and it became the best path for the fatigue crack growth. The fatigue crack tip would be connected with fractured grain boundary eventually, which led to the fast crack growth in different loading stage.